1995
DOI: 10.1017/s0022050700041061
|View full text |Cite
|
Sign up to set email alerts
|

Federal Personal Income Tax Policy in the 1920s

Abstract: During the 1920s, federal personal income tax rates, which had been dramatically increased during World War I, were sharply reduced. These tax rate cuts have often been cited as an example of a successful supply-side policy, but they have also been criticized as policies designed primarily to benefit the wealthy. We argue that a primary motive for the tax cuts of the 1920s was the desire to reduce the tax avoidance by wealthier individuals that occurred as a result of the previous tax rate increases and that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 1 publication
0
11
0
Order By: Relevance
“…But some of the avoidance they sought to reduce may have utilized the Liberty bonds. Work by Smiley and Keehn (1995) supports Mellon's argument.…”
Section: How Were Nominal Rates Kept Down During the War?mentioning
confidence: 69%
“…But some of the avoidance they sought to reduce may have utilized the Liberty bonds. Work by Smiley and Keehn (1995) supports Mellon's argument.…”
Section: How Were Nominal Rates Kept Down During the War?mentioning
confidence: 69%
“…Source: Authors, from Piketty and Saez (2003). mention a number of debates among politicians about the opportunity of taxation (Smiley and Keehn 1995); and even though important steps were realized, notably with the implementation in 1913 of the first permanent federal income tax, many rebellions and even instances of organized tax-avoidance took place. The higher-income class, whose members "received more of their income as interest and dividends and less as wages and salaries" (Smiley and Keehn 1995, p. 298), lobbied for lower taxes.…”
Section: Addressing Inequalities In a Period Of Turmoil: Small's mentioning
confidence: 99%
“…But some investigators found unexpected continuity in economic policy from the Wilson administration through the 1920s (Radner 1971;Murray 1978;Metzer 1985). Recently, economists Gene Smiley and Richard Keehn argued from statistical analysis that the need to stem tax avoidance, not political ideology, motivated the Mellon tax reforms (Smiley and Keehn 1995).…”
Section: Russell C Leffingwell Assistant Secretary In President Woomentioning
confidence: 99%